Molecular detection of hemoplasma infection among cats from São Luís island, Maranhão, Brazil - Braga, M.S.C.O. [UNESP]; André, M.R. [UNESP]; Freschi, C.R. [UNESP]; Teixeira, M.C.A. [UNESP]; Machado, R.Z. [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
Hemoplasmas are bacteria that infect erythrocytes, attaching to the red blood cell. There is a need for more reports of hemoplasma infection prevalence and molecular characterization among cats in Brazil since there are only few published reports. The present work aimed to detect and molecularly characterize the presence of hemotrophic mycoplasmas in domestic cats with outdoor access from São Luís, Maranhão, Brazil. Twenty cats (10%) were positive for Candidatus M. haemominutum, five (2.5%) for M. haemofelis, and four (2.%) for M. turicensis based on 16S rRNA gene PCRs. Five cats (2.5%) were co-positive for Candidatus M. haemominutum and M. haemofelis. PCR diagnosis was confirmed by sequencing; and phylogenetic analysis was based on 16S rRNA and rnpb genes.
Keywords: cats; Mycoplasma haemofelis; Candidatus Mycoplasma haemominutum; Candidatus Mycoplasma turicensis